The influence of preterm birth on the developing thalamocortical connectome - Ball, Gareth; Boardman, James P.; Aljabar, Paul; Pandit, Anand; Arichi, Tomoki; Merchant, Nazakat; Rueckert, Daniel; Edwards, A. David; Counsell, Serena J. (Cortex, 2013)
Introduction: Defining connectivity in the human brain signifies a major neuroscientific goal. Advanced imaging techniques have enabled the non-invasive tracing of brain networks to define the human connectome on a millimetre-scale. During early development, the brain undergoes significant changes that are likely represented in the developing connectome, and preterm birth represents a significant environmental risk factor that impacts negatively on early cerebral development. Using tractography to comprehensively map the connections of the thalamocortical unit, we aim to demonstrate that premature extrauterine life due to preterm delivery results in significantly decreased thalamocortical connectivity in the developing human neonate. Methods: T1- and T2-weighted magnetic resonance images and 32-direction diffusion tensor images were acquired from 18 healthy term-born neonates (median gestational age: 41+3) and 47 preterm infants (median gestational age: 28+3) scanned at term-equivalent age. Using a novel processing pipeline for tracing connections in the neonatal brain we map and compare the thalamocortical macro-connectome between groups. Results: We demonstrate that connections between the thalamus and the frontal cortices, supplementary motor areas, occipital lobe and temporal gyri are significantly diminished in preterm infants (FDR-corrected, p < .001). Conclusions: This supports the hypothesis that the thalamocortical system is vulnerable following preterm birth and the tractographic framework presented represents a method for analysing system connectivity that can be readily applied to other populations and neural systems. © 2012 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Connectome; Developing brain; Diffusion tractography; Preterm birth; Thalamocortical connectivity